A informação de custos como ferramenta de gestão na Universidade Federal Rural da Amazônia - SILVA, Mauricio Dias (Universidade Federal do Pará, 2019)
The present research sought to demonstrate the guidelines, challenges and implications of adopting cost management at the Federal University of Amazonia (UFRA) through the Cost Information System (SIC). It should be noted that Cost Accounting is a necessary instrument for the calculation and measurement of the results of the activities performed by the government, evaluating the achievement of the desired levels of efficiency. It seeks to focus efforts on the study of cost management, aiming at a better allocation of resources so that the economic result is increasingly positive and reverted to higher levels of excellence of the services provided by UFRA to society. Considering the existing obstacles and limitations to the operationalization of the SIC, since the utilization rate of this system by the Federal Institutions is very low, it is sought to discuss the benefits of adopting the cost information for decision making purposes by the managers, the tools available that will assist in the preparation of cost reports. The dissertation showed the reports of the implementation of the cost information system in the Central Bank of Brazil (Bacen) and in the Brazilian Communication Company (EBC), recognized as two of the best practices for implementing cost management among federal agencies, and based on these experiences and on the budgetary and patrimonial data of UFRA, models and strategies have been proposed that are adequate to their reality, within the current norms and laws. The research can be classified as applied for its exploratory characteristic and also has a multidisciplinary character. Qualitative analysis was used through bibliographical and documentary research. At the end of the research, the benefits of the operation of SIC in UFRA were ratified by presenting the successful experiences of Bacen and EBC in their cost management implementation processes, as well as the existing similarities regarding interference factors. Thus, it is concluded that the cost information extracted from the Federal Government structuring systems, using the absorptive costing method, will contribute in a relevant way to the managers of UFRA aiming at achieving excellence in the management and provision of services to the community